Clinical Outcomes and Quality of Life in Elderly Patients Treated with a Newly Designed Double Tube Endoscopy for Degenerative Lumbar Spinal Stenosis. Issue 7 (27th May 2022) - Liu, Lantao; Dong, Jian; Wang, Dechun; Zhang, Chao; Zhou, Yue
Abstract: Objective: To evaluate the clinical outcome and quality of life in elderly patients in poor conditions with unilateral symptomatic degenerative lumbar spinal stenosis (DLSS) who were treated with percutaneous endoscopic lumbar discectomy (PELD) assisted by double tubes. Methods: This study was designed retrospectively. From June 2017 to June 2018, 31 consecutive elderly patients who were presented with unilateral symptomatic DLSS, underwent PELD assisted by double tubes under local anesthesia. American Society of Anesthesiology score (ASA) was used to evaluate the patients' conditions. The operative time, intraoperative blood loss, hospital stay, and complications were evaluated. Clinical outcomes were assessed by the visual analog scale (VAS), Oswestry disability index (ODI), and modified Macnab criteria. Short Form 36 (SF‐36) was used to evaluate the life quality. The CT or MRI was used to evaluate the spinal area. Results: Thirty‐one patients were enrolled and 25 cases achieved at least a 24‐month follow‐up. Three patients were lost to follow‐up and three patients died from other diseases. A total of 76% (19/25) of the patients presented an ASA score of more than 3. The mean operative time was 67.80 min, the mean blood loss was 18.2 ml, and the hospital stay was 6.92 days. The postoperative 12‐month follow‐up VAS score significantly decreased compared with that before the operation (1.12 ± 0.73 vs. 5.12 ± 1.81, p < 0.01). Although the VAS score decreased at the final follow‐up, there was no significant difference compared with that at the 12‐month follow‐up (0.92 ± 0.64 vs. 1.12 ± 0.73, p = 0.549). So did the ODI. Also, there was no difference in the ODI scores between the 12‐month follow‐up and the final follow‐up (12.52 ± 5.58 vs. 9.44 ± 6.32, p = 0.172). The overall excellent rate was 92% (23/25) at the final follow‐up. The scores of the physical function, mental function, and social function of SF‐36 after the operation improved significantly compared with those before operation ( p < 0.05). But there was no difference in the physical function score (84.00 ± 6.29 vs 84.40 ± 6.18, p = 0.871), mental function score (81.76 ± 8.01 vs 81.68 ± 6.67, p = 0.974), or social function score (115.50 ± 13.64 vs 118.50 ± 12.03, p = 0.437) between the 12‐month follow‐up and the final follow‐up. There were no differences in the VAS, ODI, and SF‐36 between the L4/5 and L5 S1 groups before operation or at the final follow‐up ( p > 0.05). The postoperative radiology indicated the lateral recess is opened and the area of the dural sac is expanded. Two cases (8.0%, 2/25) experienced recurrence and a secondary PELD was performed. Conclusions: PELD assisted by double tubes is effective for unilateral symptomatic DLSS in elderly patients with comorbidities and could improve life quality. Abstract : PELD assisted by ZESSYS is effective for unilateral symptomatic DLSS in elderly patients with comorbidities and could improve life quality.